UKURAN PERUSAHAAN MODAL KERJA DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022-2023 - Radja, Asmirayanti Ina; Pramitasari, Triska Dewi; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to determine the effect of the Company Size Working Capital and Leverage on the Company Value with Profitability as an Intervening Variable in Food and Beverage Sub-Sector Companies registered on the IDX for the period 2022-2023. The population in this study was all food and beverage manufacturing companies registered on the IDX for the period 2022-2023, totaling 23 companies. The sampling technique was determined using purposive sampling so that 15 samples were obtained which would be used for data analysis. The data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the PLS 3.0 application, showed that the Company Size has a significant negative effect on Profitability, the Working Capital has a negative but insignificant effect on Profitability, the Leverage has a negative but insignificant effect on Profitability, the Company Size has a significant negative effect on Company Value, the Working Capital has a positive but insignificant effect on Company Value, the Leverage has a negative but insignificant effect on Company Value, the Profitability has a significant negative effect on Company Value. The results of the indirect influence test showed that the Company Size has a significant positive effect on Company Value through Profitability, the Working Capital has a positive but insignificant effect on Company Value through Profitability, and the Leverage has a positive but insignificant effect on Company Value through Profitability.